Shoulder design developments for FSW lap joints of dissimilar polymers. (October 2015) - Eslami, Shayan; Ramos, Tiago; Tavares, Paulo J.; Moreira, P.M.G.P.
Graphical abstract: Highlights: Innovative tool for friction stir welding of polymers in lap configuration. Assessment of the effect of different materials for stationary shoulder and probe geometries. Comparison between conventional and stationary FSW tools. Abstract: This paper describes the process of developing a stationary FSW tool for welding thin plates of dissimilar polymers. Previous FSW research seems to be still far from the type of systematic engineering approach that leads to consistent results, in particular for polymeric materials and especially for lap joining of polymers. This study is focused on the development of welding tools, aiming at sound and robust friction stir welding of dissimilar polymeric materials in lap joint configuration. Different materials and geometries have been tested in order to analyse quality of the welds and appearance. It has been verified that stationary shoulders made out of polymer materials give the best result. The welds produced with this tool improved the welds surface quality and strength significantly. The use of the proposed tool showed to improve the stability in the axial force magnitude during the welding procedure in comparison with a conventional FSW tool.